Gastrointestinal barriers to levodopa transport and absorption in Parkinson's disease - Leta, Valentina; Klingelhoefer, Lisa; Longardner, Katherine; Campagnolo, Marta; Levent, Hafize Çotur; Aureli, Federico; Metta, Vinod; Bhidayasiri, Roongroj; Chung‐Faye, Guy; Falup‐Pecurariu, Cristian; Stocchi, Fabrizio; Jenner, Peter; et al. (European journal of neurology, 2023)
Levodopa is the gold standard for the symptomatic treatment of Parkinson's disease (PD). There are well documented motor and non‐motor fluctuations, however, that occur almost inevitably once levodopa is started after a variable period in people with PD. Whilst brain neurodegenerative processes play a part in the pathogenesis of these fluctuations, a range of barriers across the gastrointestinal (GI) tract can alter levodopa pharmacokinetics, ultimately contributing to non‐optimal levodopa response and symptoms fluctuations. GI barriers to levodopa transport and absorption include dysphagia, delayed gastric emptying, constipation, Helicobacter pylori infection, small intestinal bacterial overgrowth and gut dysbiosis. In addition, a protein‐rich diet and concomitant medication intake can further alter levodopa pharmacokinetics. This can result in unpredictable or sub‐optimal levodopa response, ‘delayed on’ or ‘no on’ phenomena. In this narrative review, we provided an overview on the plethora of GI obstacles to levodopa transport and absorption in PD and their implications on levodopa pharmacokinetics and development of motor fluctuations. In addition, management strategies to address GI dysfunction in PD are highlighted, including use of non‐oral therapies to bypass the GI tract.